Spirit (shen), styles of knowing, and authority in contemporary Chinese medicine - Hsu, E (Springer, 2000)
Studies on the terminology of expert knowledge tend to neglect the relevance of sociological data, in spite of general acceptance that knowledge and social practice are interdependent. This paper explores expert knowledge and practice by examining ‘styles of knowing’ and how they differ according to the ways in which experts establish their authority. For assessing medical authority in microsocial settings, the author takes recourse to Weber’s three ideal types. The study shows that for a charismatic healer who seeks to reach mutual consensus with his clientele vagueness in terminology can be useful. When, however, medical authority depends on recognition by superiors and peers in modern bureaucratic institutions, vague terms tend to be avoided. So, the same term that a charismatic healer may refer to in a vague sense becomes more explicitly defined in the bureaucratic setting. Its sense is more clearly delimited and denotational qualities are emphasized. In institutions where traditional authority prevails, like those of the literate elite in highly stratified traditional societies, the technical terminology is not only vague, but notoriously polysemous. The article draws on ethnographic data of Chinese medicine and qigong therapy as practised in the late eighties in Kunming city, the capital of Yunnan province in the People’s Republic of China, but it is meant to contribute in a more general way to an exploration of the ways in which claims to medical authority interrelate with word meaning, language use, and ‘styles of knowing’. The term investigated, shen, refers to the spiritual, a domain of human experience that is widely acknowledged by traditional medical practitioners, but difficult to evaluate by sociological analysis.